Habituation of National Character Values Through Cultural Literacy Activities at SMP Negeri 6 Mataram - Maylani, Annisa; Sawaludin, Sawaludin; Alqadri, Bagdawansyah; Yuliatin, Yuliatin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Cultural literacy activities are activities that refer to the understanding of values, norms, and habits the purpose of this study is to find out how the habituation of national character values through cultural literary activities and to find out what the impact of the habituation of national character values through cultural literacy activities at SMPN 6 Mataram. This study uses a descriptive research type with a qualitative approach. Data collection techniques and documentation techniques. Data analysis techniques use the miles and hubermen technique, namely data reduction, data presentation and data conclusion. Data validity techniques use time, source, and technique triangulation. Based on the data obtained, the habituation of cultural literacy activities can be carried out through several activities, namely: 1) intracurricular activities; 2) extracurricular activities; and 3) co-curricular activities. The values of national character after habituation are: tolerance, discipline, creative, love of country, friendly/communicative, like the read, and responsibility. The positive impacts of habituating national character values through cultural literacy activites are: 1) increasing interest and literacy habits; 2) fostering a sense of joy towards local culture; 3) increasing enthusiasm for learning; 4) developing creativity; while the negative impacts are: 1) decreasing student motivation; and 2) limited time.